Research progress in bioflocculants from bacteria - Al-Mamun, Abdullah; Hassan, Hamidah; Alam, Md Zahangir (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Although one of the major users of flocculants are water and wastewater treatment industries, flocculants are also used in various food industries. The chemical flocculants are preferred widely in these industries due to low production cost and fast production ability. However, the negative effects of the chemical flocculants should not be neglected to gain the economic benefits only. Therefore, the researchers are working to discover efficient and economical flocculants from biological sources. Several attempts have been made and are still being made to extract or produce bioflocculants from natural sources such as plants, bacteria, fungi, yeast, algae, etc. The review revealed that significant amount of work have been done in the past, in search of bioflocculant. However, commercially viable bioflocculants are yet to be marketed widely. With the advent of new biotechnologies and advances in genetic engineering, the researchers are hopeful to discover or develop commercially viable, safe and environmentfriendly bioflocculants